Community pharmacist-and psychologist-led program of neuropsychological screening in the aftermath of the COVID-19 pandemic: A cross-sectional survey - Nicola Luigi BRAGAZZI; Fiorella PALOMBO-FERRETTI; Rocco CARBONE; Tania Simona RE; "Pharmacists- and Psychologists in community pharmacies-led Psychological Screening for Cognitive issues in the aftermath of the COVID-19 pandemic" (PsyChOVID) WORKING GROUP (Journal of Health and Social Sciences)
Background: Early detection and diagnosis of cognitive impairment are paramount to improving the clinical outcomes and care of patients. Whilst primary care professionals play a key role in the healthcare management and treatment of their patients, community pharmacists and other allied health professionals working in community pharmacies are more accessible and trusted. As such, they are in an ideal position to identify and assist in the management of individuals with cognitive memory disorders. Aim: To assess the impact of a pharmacist-based cognitive memory screening service delivered in community pharmacy practice in Italy in the aftermath of the COVID-19 pandemic. Design: Cross-sectional questionnaire-based survey. Setting: Community pharmacies. Population: Patients accessing community pharmacies. Methods: Participants underwent a comprehensive neuropsychological screening program (the “Montreal Cognitive Assessment” (MoCA) test, the “Babcock Story Recall Test”, and the “Rey–Osterrieth complex figure” (ROCF) test). The accuracy, sensitivity, and specificity of the classical medical/psychological referral for cognitive impairment were computed. Results: A sample of 185 subjects (aged 61.24±15.06 years, 78.9% females) was recruited. The classical medical/psychological referral yielded an accuracy ranging from 58.4% to 63.2%, a sensitivity of 56.3-66.7%, and a specificity of 57.9-74.0% in terms of detection of individuals with cognitive impairment. The neuropsychological screening enabled the identification of a further 33.3-43.8% of subjects that would have been missed otherwise. Conclusions: Neuropsychological screening programs in the setting of community pharmacies are highly valuable and effective.